Molecular Precursors of the RNA-World in Space: New Nitriles in the G+0.693−0.027 Molecular Cloud - Rivilla, Víctor M.; Jiménez-Serra, Izaskun; Martín-Pintado, Jesús; Colzi, Laura; Tercero, Belén; de Vicente, Pablo; Zeng, Shaoshan; Martín, Sergio; García de la Concepción, Juan; Bizzocchi, Luca; Melosso, Mattia; Rico-Villas, Fernando; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Nitriles play a key role as molecular precursors in prebiotic experiments based on the RNA-world scenario for the origin of life. These chemical compounds could have been partially delivered to the young Earth from extraterrestrial objects, stressing the importance of establishing the reservoir of nitriles in the interstellar medium. {\bf We report here the detection towards the molecular cloud G+0.693-0.027 of several nitriles, including cyanic acid (HOCN), and three C$_4$H$_3$N isomers (cyanoallene, CH$_2$CCHCN; propargyl cyanide, HCCCH$_2$CN; and cyanopropyne (CH$_3$CCCN), and the tentative detections of cyanoformaldehyde (HCOCN), and {\bf glycolonitrile} (HOCH$_2$CN)}. We have also performed the first interstellar search of cyanoacetaldehyde (HCOCH$_2$CN), which was not detected. Based on the derived molecular abundances of the different nitriles in G+0.693-0.027 and other interstellar sources, we have discussed their formation mechanisms in the ISM. We propose that the observed HOCN abundance in G+0.693-0.027 is mainly due to surface chemistry and subsequent shock-induced desorption, while HCOCN might be mainly formed through gas-phase chemistry. In the case of HOCH$_2$CN, several grain-surface routes from abundant precursors could produce it. {\bf The derived abundances of the three C$_4$H$_3$N isomers in G+0.693-0.027 are very similar, and also similar to those previously reported in the dark cold cloud TMC-1}. This suggests that the three isomers are likely formed through gas-phase chemistry from common precursors, possibly unsaturated hydrocarbons (CH$_3$CCH and CH$_2$CCH$_2$) that react with the cyanide radical (CN). The rich nitrile feedstock found towards G+0.693 confirms that interstellar chemistry is able to synthesize in space molecular species that could drive the prebiotic chemistry of the RNA-world.